Comparing palliation strategies for single-ventricle anatomy with transposed great arteries and systemic outflow obstructionCentral MessagePerspective - Alyssa B. Kalustian, MD; Zachary A. Spigel, MD; Christopher E. Greenleaf, MD; Tam T. Doan, MD; Alejandra I. Chavez, MD; Iki Adachi, MD; Jeffrey S. Heinle, MD; Ziyad M. Binsalamah, MD (JTCVS Techniques)
Objective: Patients with complex single-ventricle anatomy with transposed great arteries and systemic outflow obstruction (SV-TGA-SOO) undergo varied initial palliation with ultimate goal of Fontan circulation. We examine a longitudinal experience with multiple techniques, including the largest published cohort following palliative arterial switch operation (pASO), to describe outcomes and decision-making factors. Methods: Neonates with SV-TGA-SOO who underwent initial surgical palliation from 1995 to 2022 at a single institution were retrospectively reviewed. Results: In total, 71 neonates with SV-TGA-SOO underwent index surgical palliation at a median age of 7 days (interquartile range, 6-10) by pASO (n = 23), pulmonary artery band (PAB) with or without arch repair (n = 25), or modified Norwood with Damus–Kaye–Stansel aortopulmonary amalgamation (n = 23). Single-ventricle pathology included double-inlet left ventricle (n = 37, 52%), tricuspid atresia (n = 27, 38%), and others (n = 7, 10%). All mortalities (n = 5, 7%) occurred in the first interstage period after PAB (n = 3) and Norwood (n = 2). Subaortic obstruction in the PAB group was addressed by operative resection (n = 10 total, 7 at index operation) and/or delayed aortopulmonary amalgamation (n = 13, 52%). Two patients with pASO (9%) had early postoperative coronary complications, 1 requiring operative revision. Median follow-up for survivors was 10.4 years (interquartile range, 4.5-16.6 years). Comparing patients by their initial palliation type, notable significant differences included size of bulboventricular foramen, weight at initial operation, operation duration, postoperative length of stay, time to second-stage palliation, multiple pulmonary artery reinterventions, and left pulmonary artery interventions. There were no significant differences in overall survival, Fontan completion, reintervention-free survival in the first interstage period, pulmonary artery reintervention-free survival, long-term systemic valve competency, or ventricular dysfunction. Conclusions: Excellent mid- to long-term outcomes are achievable following neonatal palliation for SV-TGA-SOO via pASO, PAB, and modified Norwood, with comparable survival and Fontan completion. Initial palliation strategy should be individualized to optimize anatomy and physiology for successful Fontan by ensuring an unobstructed subaortic pathway and accessible pulmonary arteries. pASO is a reasonable strategy to consider for these heterogeneous lesions.